Silyl Cyanopalladate-Catalyzed Friedel–Crafts-Type Cyclization Affording 3-Aryloxindole Derivatives - Ece, Hamdiye; Tange, Yuji; Yurino, Taiga; Ohkuma, Takeshi (Synlett, 2021)
3-Aryloxindole derivatives were synthesized through a Friedel–Crafts-type cyclization. The reaction was catalyzed by a trimethylsilyl tricyanopalladate complex generated in situ from trimethylsilyl cyanide and Pd(OAc)2. Wide varieties of diethyl phosphates derived from N-arylmandelamides were converted almost quantitatively into oxindoles. When N,N-dibenzylamide was used instead of an anilide substrate, a benzo-fused δ-lactam was obtained. An oxindole product was subjected to substitution reactions to afford 3,3-diaryloxindoles with two different aryl groups.
Keywords: Lewis acid catalysis; Friedel–Crafts reaction; cyclization; oxindoles; SN1 reaction